2013
DOI: 10.3233/jvr-130628
|View full text |Cite
|
Sign up to set email alerts
|

Economic and programmatic indicators explain vocational rehabilitation employment rates of persons with cognitive disabilities

Abstract: This national study investigated state economic health and state Vocational Rehabilitation (VR) services for persons with cognitive disabilities. Using 2004 to 2010 extant data from the Rehabilitation Services Administration(RSA) and the U.S Bureau of Labor Statistics (BLS) and the U.S. Census Bureau, this study explains variability in state VR services employment outcomes based on state economic performance and state-level VR factors. The results show state economic performance explains a significant amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Further research supports the claim that the overall influence of the employment rate is impacted at both agency and personal levels (Nord et al, 2013). Nord and colleagues (2013) found that when the overall employment rate was high employment outcomes of individuals utilizing VR services also increased.…”
Section: Labor Marketmentioning
confidence: 62%
See 4 more Smart Citations
“…Further research supports the claim that the overall influence of the employment rate is impacted at both agency and personal levels (Nord et al, 2013). Nord and colleagues (2013) found that when the overall employment rate was high employment outcomes of individuals utilizing VR services also increased.…”
Section: Labor Marketmentioning
confidence: 62%
“…Further, Honeycutt and others (2015) found that overall agency resources as associated with a status of OOS may contribute to differences in employment outcomes among state VR agencies. Other research has confirmed that state-level economic factors such as the unemployment rate influence VR services and employment outcomes (Nord et al, 2013). By building off of these works, the aim of this study is to seek how state VR agency differ across personal characteristics, agency level and state-economic factors.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations